Health-related quality of life in patients with gastro-oesophageal reflux disease under routine care: 5-year follow-up results of the ProGERD study - Nocon, M.; Labenz, J.; Jaspersen, D.; Leodolter, A.; Richter, K.; Vieth, M.; Lind, T.; Malfertheiner, P.; Willich, S. N. (Alimentary Pharmacology & Therapeutics, 2009)
Background : Gastro-oesophageal reflux disease (GERD) is a common disorder associated with substantial reductions in health-related quality of life (HRQL). Aim : To describe patterns of change in HRQL during 5 years of follow-up in a large population of GERD patients. Methods : In 2000, a total of 6215 GERD patients were enrolled in the Progression of GERD (ProGERD) study. During follow-up, patients received any medication considered necessary. HRQL was assessed yearly with the Short-Form 36 and the Quality of Life in Reflux and Dyspepsia (QOLRAD) questionnaires. Associations between patient characteristics and changes in HRQL were analysed using multiple logistic regression models. Results : After 5 years, data on HRQL were available for 4597 (74%) patients. Both generic and disease-specific HRQL improved after baseline and remained well above baseline levels in the following years. A clinically relevant decrease in QOLRAD scores was reported by 3-5% of patients. According to our multivariate analysis, a decrease in HRQL was associated with a higher reflux symptom load and the presence of night-time heartburn. Conclusions : Only a small minority of the ProGERD population reported a clinically relevant decrease in HRQL, which was associated most strongly with nocturnal heartburn. © 2009 Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2025-03-05